A clinicopathological study of skin tumors from a tertiary care centre in North India - Palvi Goel; Sukhjot Kaur; Avantika Garg; Jaskaran Batra; Bhawna Garg; Neena Sood (Wolters Kluwer Medknow Publications, 2021)
Background: There is a huge spectrum of skin tumors which can be confused clinically with malignancies, particularly when they are pigmented or inflamed, and histopathological examination of a biopsy specimen is required to establish a definitive diagnosis and to facilitate appropriate intervention and follow up. Aim: To evaluate all skin tumors and categorize them according to their origin. Methods: The present study was conducted over a period of 4 years (July 1, 2013 to June 31, 2017) comprising of 1.5 years prospective and 2.5 years retrospective analysis in the departments of Dermatology and Pathology, at a tertiary hospital in North India. All specimens of skin tumors were analyzed grossly and microscopically. Immunohistochemistry was done wherever possible. Results: A total of 232 skin tumors were seen; of which 123 cases were benign (53.0%) and 109 cases were malignant (47.0%). The mean age of patients with benign and malignant skin tumors was 40.3 ± 19.9 and 60.8 ± 14.8 years, respectively. The most common site was face (n = 106; 45.7%) followed by limbs (n = 44; 19.0%). The male:female ratio of benign and malignant tumors was 1.01:1 and 1.31:1, respectively. Among the benign tumors, keratinocytic tumors were the commonest (n = 57; 46.3%) followed by the melanocytic tumors (n = 37; 30.1%) and appendageal tumors (n = 29; 23.6%). The most common malignant skin tumors were the keratinocytic tumors (n = 87; 79.8%) followed by 12 cases (11%) of hematolymphoid tumors and five cases (4.6%) each of melanocytic and appendageal tumors. Limitations: The lack of clinical and dermatoscopic correlation and inclusion of retrospective data are the limitations of this study. Conclusions: Skin tumors affect people of all ages. The benign tumors are seen in the younger age group as compared to malignant tumors. Face is the most common site and keratinocytic tumors are the most common skin tumors in both benign and malignant categories.